Reading Psalm 109 in African Christianity - Adamo, David T. (Old Testament Essays, 2008)
Psalm 109 is one of the most problematic psalms in the Old Testament. The majority of scholars are not comfortable as far as the interpretation of the contents is concerned. It is one of the psalms that is classified as an imprecatory psalm dealing with vengeance against enemies instead of forgiveness. It has been given various names among some Western scholars, who link the psalm to hate, vengeance, cursing, and violence. However, when approached from an Africentric point of view in African Christianity, this psalm can be is considered as one of the prayers of appeal to God for justice. The purpose of this article is to discuss how this psalm is interpreted differently in African Christianity, for example as a psalm of protection, success, healing and, mostly, as a prayer to God to get up and fight for the righteous and the poor instead of leaving the fight to the sufferer visiting witch doctors, herbalists, or evil ones.
free